Optimization of Hijab Production Profits for UMKM Saveer Hijab Using the CPLEX Application - Julianti, Shofia Rizka; Dwi Agustina Kurniawati; Noor Saif Muhammad Mussafi (Journal of Industrial Engineering and Halal Industries, 2025)
Micro, Small, and Medium Enterprises play a major role in economic growth in Indonesia and must continue to be supported and developed in order to compete at a global level. Saveer Hijab is one of the hijab fashion brands in the MSME sector that produces various types of hijab. Saveer Hijab experienced a decline in sales because the number of requests was not balanced with production costs due to the increase in raw material prices. This study aims to formulate an optimization model to determine the optimal production volume so that maximum profit is obtained using the CPLEX application. The results of the study showed that to optimize profits, Saveer Hijab must produce 200 pcs of Malay Scarf hijab and 120 pcs of Pashmina Square hijab. Thus, the profit obtained by Saveer Hijab is IDR 7,000,000.00 or 75%. Saveer Hijab obtains maximum efficiency for the amount of fabric and thread inventory, because in the production process of both types of hijab, it requires a fabric inventory of 500 m and a thread of 800 m, which is in accordance with the amount of material availability capacity. Furthermore, the amount of plastic packaging inventory still leaves 180 pcs because in the production process the amount of plastic used is 320 pcs.